2008
DOI: 10.1016/j.jaad.2007.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and partner moderator variables increase self-efficacy of performing skin self-examination

Abstract: Objective-We sought to identify relationship and partner-related moderating variables that influence the effectiveness of both a couples and a solo learning intervention designed to increase skin self-examination behavior in a sample of patients at risk for developing melanoma.Methods-Patients received a brief intervention designed to teach skin self-examination skills and were randomly assigned into either a solo learning condition where the intervention was administered to the patient alone (n = 65) or a cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 26 publications
5
45
0
Order By: Relevance
“…Interventions aimed at improving patient self-efficacy for SSE found that people in relationships with motivated partners who perceived being in a high-quality relationship, showed greatest improvements in self-efficacy [10]. Improving self-efficacy is important for increasing quality of skin self-examination, but improving people’s ability to identify atypical nevi specifically is a different challenge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions aimed at improving patient self-efficacy for SSE found that people in relationships with motivated partners who perceived being in a high-quality relationship, showed greatest improvements in self-efficacy [10]. Improving self-efficacy is important for increasing quality of skin self-examination, but improving people’s ability to identify atypical nevi specifically is a different challenge.…”
mentioning
confidence: 99%
“…Collective effort can be effective even when a single person has low reliability at a task, as the pattern of the group overcomes the limitations of each individual. In the case of skin cancer prevention and skin self-examination, motivation has been suggested as a key moderator in improving relevant outcomes [10], and crowdsourcing approaches to decision making take advantage of collective motivation, as participation is voluntary, to engage in classification tasks.…”
mentioning
confidence: 99%
“…Similarly, though prior research has most commonly focused on college women, the current study did not find moderator effects by age, education level, difficulty living on income, or health literacy. Prior studies of moderation in skin cancer prevention interventions have focused primarily on relationship variables in dyadic interventions including patients and partners or children and parents (Hultgren, Turrisi, Mallett, Ackerman, & Robinson, 2016; Robinson, Stapleton, & Turrisi, 2008; Turrisi, Hillhouse, Robinson, Stapleton, & Adams, 2006). However, one study found that an appearance-focused workbook reduced indoor tanning specifically among low-knowledge female college indoor tanners (Stapleton, Turrisi, Hillhouse, Robinson, & Abar, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al 2007, Robinson et al 2008, Mesters et al 2009, Mujumdar et al 2009, Glanz et al 2010, Coups et al 2011, Kasparian et al 2012, Körner et al 2013 Figure 2 Summary of the barriers and levers to skin self-examination identified from the literature.…”
Section: Instrument Developmentmentioning
confidence: 99%